Characterization and Properties of Sri Lankan Coir Fibre - Dineth S. Samarawickrama (International Coconut Community, 2010)
This study mainly concentrated on revealing the scientific data on the properties of Sri Lankan coir fibre and classifying them into different grades based on scientific parameters instead of visual observations to establish quality specifications for the coir fibre industry in Sri Lanka. Critical parameters were studied for suitability of the industrial applications. Size distribution and average length of different fibres were determined by the frequency distribution method, to be used as industrial oriented parameters. The weighted average breaking load of coir fibre was determined using the universal tensile strength tester. As per the result, coir fiber has an elongation property of about 20-28%. Also, coir fibre is a highly resilient natural fibre and Omat coir fibre had the highest value among other coir fibre types. Porous microstructure of the coir fibre was observed through the scanning electron microscopy and hygroscopic characteristics described according to the structure. The moisture equilibrium values of coir fibre in Sri Lanka were observed at 15-18% and it was achieved by sun drying. This moisture levels avoid the heavy condensation during transportation particularly in countries with cold climate. Properties of coir fibre found in the study were used in the establishment of the National Quality Standard specifications for mechanically extracted coir fibre in Sri Lanka.